The Internationalization of Renminbi - Erlangga Arbi Prakoso; Makmur Keliat; Fredy Buhama Lumban Tobing (Intermestic: Journal of International Studies, 2019)
After global financial crisis 2008, the position of the US dollar began to be debated and led to the narrative of the internationalization of renminbi. This literature review discusses how the literatures has evolved regarding internationalization of renminbi. Based on the taxonomy method, this literature review finds three major themes: China’s interest, implementation process, and external reactions. Based on those three themes, this literature review argues that internationalization of renminbi occurs because the character of international relations tends to be competitive due to power relations. This condition triggered the adjustment of Chinese interests according to Chinese characteristics using offshore renminbi centers. Besides using the supply-side approach as the dominant approach, this literature review identifies an increase in discussion after 2009 and also finds approach and empirical gap that use demand-side approach of international actors. This paper contributes to the study of international political economy related to state and market logic.